2007
DOI: 10.1042/ba20060085
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba leaf extract (EGb 761) diminishes adriamycin‐induced hyperlipidaemic nephrotoxicity in rats: association with nitric oxide production

Abstract: The aim of this experimental study was to investigate the effect of a standardized preparation of Ginkgo biloba extract (EGb 761) on the hyperlipidaemic nephrotoxicity and oxidative stress induced by a single intravenous injection (5 mg/kg) of adriamycin. EGb 761 was received daily thereafter by a gavage at the dose of 100 mg/kg for 35 consecutive days. EGb 761 administration significantly attenuated adriamycin-induced renal dysfunction, as assessed by measuring serum lipid profile, serum total protein, serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The GB improved the renal function in the MTX group confirming its nephroprotective effect and this was in harmony with other studies that reported amelioration of the renal function with the GB administration in models of diabetic nephropathy [10] as well as models of induced nephrotoxicity by cisplatin [30], adriamycin [31], and MTX [4].…”
Section: Discussionsupporting
confidence: 88%
“…The GB improved the renal function in the MTX group confirming its nephroprotective effect and this was in harmony with other studies that reported amelioration of the renal function with the GB administration in models of diabetic nephropathy [10] as well as models of induced nephrotoxicity by cisplatin [30], adriamycin [31], and MTX [4].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, Ginkgo biloba has a vascular rescuing effect as well as an antiapoptotic effect [ 11 13 ]. In addition, it has been shown that Ginkgo biloba could rescue renal injury in brain death induced-nephrotoxicity [ 14 ] and adriamycin-induced hyperlipidemic nephrotoxicity [ 15 ] and in uranium-treated mice [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports showed an effective protective effect of GIN in different models of neurotoxicity 26 and hepatotoxicity, 27 in addition to nephrotoxicity. 28 , 29 Moreover, the protective effect of GIN against testicular toxicity induced by cisplatin, 25 doxorubicin, 30 cadmium, 31 and cellphone radiation 32 was reported. Nevertheless, the impact of GIN versus MTX-induced gonadotoxicity is still not been identified yet.…”
Section: Introductionmentioning
confidence: 99%